Inisiasi Program KUPAT (Aku Paham Amanat Guruku) sebagai Tawaran Alternatif Peningkatan Level Literasi Informasi Pelajar - Rahayu, Titik Ayu Sri; Satria, Faudyan Eka (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The School Literacy Movement has recently become a popular agenda in every school in Indonesia. This is to develop the students’ character through acculturating the school literacy ecosystem which is realized in the School Literacy Movement that leads them to become lifelong learners. However, in the case of Sekolah Dasar Negeri (SDN) 2 Werungotok in Nganjuk Regency, there is an impetus that makes the literacy movement program must be specific because of the lack of students who are classified as having proficient literacy skills. Through this scientific report, the researcher wants to promote an alternative agenda to improve literacy skills for students, especially in the aspect of information literacy. The agenda is called KUPAT (I Understand My Teacher's Mandate). By adapting the classroom action research method, this paper aims to present data and analysis on how far the KUPAT program can improve the literacy skills of students at SDN 2 Werungotok. Based on observations of 154 students at SDN 2 Werungotok, this report shows that the KUPAT Program's writing and listening activities positively correlate with their ability to process and explore the message of information, especially from the messages given by the master of ceremonies on Monday.